2010
DOI: 10.1371/journal.pone.0011703
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Rheumatoid Arthritis Shared Epitope Binding Site on Calreticulin

Abstract: BackgroundThe rheumatoid arthritis (RA) shared epitope (SE), a major risk factor for severe disease, is a five amino acid motif in the third allelic hypervariable region of the HLA-DRβ chain. The molecular mechanisms by which the SE affects susceptibility to – and severity of - RA are unknown. We have recently demonstrated that the SE acts as a ligand that interacts with cell surface calreticulin (CRT) and activates innate immune signaling. In order to better understand the molecular basis of SE-RA association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 40 publications
(73 reference statements)
2
59
0
1
Order By: Relevance
“…The expectation would be that an antigen that is highly homologous to the vertebrate protein might be a poor antigen in that it might be recognized as self and thus not stimulate a robust antibody response as is observed with tick and other parasite CRT proteins.. It is also notable that human CRT acts as an auto-antigen in autoimmune diseases such as rheumatoid arthritis, complete congenital heart block, and coeliac disease (Holoshitz et al, 2010, Ling et al, 2010). In mice, cross-reactivity of antibodies to T. cruzi CRT with the mouse CRT protein was advanced as a possible explanation for the observed chagasic autoimmunity (Teixeira et al, 2011, 2012, Machado et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The expectation would be that an antigen that is highly homologous to the vertebrate protein might be a poor antigen in that it might be recognized as self and thus not stimulate a robust antibody response as is observed with tick and other parasite CRT proteins.. It is also notable that human CRT acts as an auto-antigen in autoimmune diseases such as rheumatoid arthritis, complete congenital heart block, and coeliac disease (Holoshitz et al, 2010, Ling et al, 2010). In mice, cross-reactivity of antibodies to T. cruzi CRT with the mouse CRT protein was advanced as a possible explanation for the observed chagasic autoimmunity (Teixeira et al, 2011, 2012, Machado et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…40 The SE binding site on CRT has been recently mapped to a well-defined region in the P-domain of the molecule. 25 Directly relevant to the MHC Cusp theory, our recent data show that the SE ligand activates an important immune regulatory function through its effect on dendritic cells (DCs). DCs have a central role in immune tolerance and T cell regulation.…”
Section: The Rheumatoid Arthritis Shared Epitope: a Prototypic Cusp Lmentioning
confidence: 99%
“…14 We have recently identified the SE as a ligand that binds to cell surface calreticulin and activates pro-osteoclastogenic signalling. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Using cell-free synthetic ligands expressing the SE motif, we have demonstrated that the SE enhanced Th17 polarisation 24 and directly activated OC differentiation. 26 When administered in vivo to mice with collagen-induced arthritis, the SE ligand enhanced joint inflammation, increased the abundance of tissue and bone marrow OCs, and enhanced bone damage in arthritic joints.…”
Section: Key Questionsmentioning
confidence: 92%